(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In the present study, metformin hydrochloride loaded microspheres were prepared for filling into the periodontal pockets with or without grafts for the treatment of periodontitis. For this purpose, chitosan was chosen as polymer and used at different drug/polymer ratios in preparation of microspheres by emulsion cross-linking method. Optimization was carried out by implementing three-factor three-level Box–Behnken design. Mathematical models were generated by regression analysis for responses of particle size (PS) and entrapment efficiency (EE). The experimental design took into account for the preparation of optimized formulation with maximum %EE and minimum PS at optimum process conditions for the microsphere formulation by reduction in chemical use and formulation time, in an economical way. The optimized formulation was selected on the basis of the desirability function and was further evaluated with respect to the particle size, entrapment efficiency, in vitro drug release, differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) spectroscopy and surface morphology studies. The results of release studies were evaluated kinetically and statistically. Particle size and entrapment efficiency of the selected batch were found to be in the range of 40.2- 59.6µm and 85- 95% respectively. The DSC studies revealed molecular dispersion and conversion of the drug into amorphous form. Surface morphology of microspheres was analyzed by scanning electron microscopy (SEM) and found to be spherical in shape with smooth surface. The mean particle size, EE, and in-vitro drug release of the optimized batch were found to be 51.4 ± 4.8µm, 96.5± 1.42%, and 79.8 ± 3.1% respectively. The release kinetics showed that the release followed the Peppas model, and the main mechanism of drug release was diffusion. These sustained release chitosan microspheres could be a promising drug delivery system for local delivery of metformin hydrochloride in the treatment of periodontitis.